The town that food saved : how one community found vitality in local food - Hewitt, Ben, 1971- (Rodale : Distributed to the trade by Macmillan, 2009)
The captivating story of a small town coming back to life, grounded in an idea that will revolutionize the way we eat. Over the past 3 years, Hardwick, Vermont, a typical hardscrabble farming community of 3,000 residents, has jump-started its economy and redefined its self-image through a local, self-sustaining food system unlike anything else in America. Even as the recent financial downturn threatens to cripple small businesses and privately owned farms, a stunning number of food-based businesses have grown in the region. The mostly young entrepreneurs have created a network of community support; they meet regularly to share advice, equipment, and business plans, and to loan each other capital. Hardwick is fast becoming a model for other communities to replicate its success.--From publisher description.